Sustainable Development a common goal: Response of Indian corporates to meet the world expectation - sharma, indu (Journal of Contemporary Research in Management (JCRM), 2013)
This paper examines the role of corporates in Sustainable Development. The two terminologies are interrelated to each other and play strong role in presence and absence of each other.An exploratory research is conducted as the purpose of research is to gain familiarity with a phenomenon and also to acquire new insight into it in order to formulate a more precise study. Data collection was secondary and informal interviews and discussions. Data was obtained from 50 corporates who have adopted this as business strategy to achieve the real goal: People, Profit and Planet. (Timothy F. Slaper, Ph.D., Tanya J. Hall, IBR 2011) As per a study done by KPMG across the globe 60% of the corporates using Sustainability as a Strategy and 50% of the world doesnâ€™t even respond to this. India being a country aiming high in terms of economic development; how it is responding to the changing requirement and Development for Sustainability is matter for concern for the generations of today and generations to come. Every stakeholder has a role to play and therefor across the globe many activities have taken place to reassure that world is aligned for a common goal. This has become part of a corporate strategy and corporates are reinforcing it as a Brand enhancement tactic also. The response of the various stakeholders is yet to be aligned. Reading the Gaps of what is sustainability and how it is perceived this paper would try explaining. Redefining of sustainability would be for the better alignment for a sustainable strategy is possible. Sustainability is about giving the unborn a world which is liveable contrary to better then today. As per the study done it is interpreted to be unachievable till all the resources are focused on a clear strategy for a better world. The amount of harm done and the corrective measures, and to avoid the future harm requires lots of work and integration of many things. It requires lots of time, money and manpower. We are buckling our shoes to chase the â€œunstoppableâ€. And the irony is: Unstoppable is due to our own efforts. The paper contributes in terms of identifying the frame work, latest trends and findings to draw certain tangents. The word â€œCorporate Sustainabilityâ€ with no formal definition given is a Business for some, Challenge for the world, being coincidently and optimistically achieved by many. The world is changing, efforts have increased, results are measured still this race is on for Strategies for PROFIT by default ignoring the fashionable word â€œPeople, Profit and Plantâ€. (Timothy F. Slaper, Ph.D., Tanya J. Hall, IBR 2011) Sustainability and Sustainable Development are topics of concern to the world forum and related organisations who are working towards sustainable development. People and companies invest in sustainability because of benefits such as improved public opinion, customer relations, and the ability to attract and retain talent (Fox, 2008). The paper has implication for the manner in which practitioners view the respective roles, significance and how resources can be aligned towards better management and sustainable approach for Indian companies. Keywords: Sustainability, Sustainable Development, Corporates, Strategy, People, Profit and Plant, Stakeholders.